Assessing the prevalence of meeting physical activity recommendations among U.S. healthcare workers: Data from the 2015 National Health Interview Survey. Issue 7 (2nd October 2020) - Song, MinKyoung; Nam, Soohyun; Buss, Julia; Lee, Soo-Jeong
Abstract: We examined the prevalence of U.S. healthcare workers who met the 2008 Physical Activity Guidelines for Americans (2008 Guidelines), and the relationships among meeting the 2008 Guidelines and health behaviors, musculoskeletal symptoms, and occupational- and workplace- factors. We estimated prevalence of meeting the 2008 Guidelines for aerobic and muscle-strengthening activity using data from the 2015 National Health Interview Survey. Among 1, 502 U.S. healthcare workers, 56.2% met the recommended guideline for aerobic activity; 30.1% met the recommended guideline for muscle-strengthening activity; and 25.3% met both recommended guidelines. Adjusting for covariates, meeting the 2008 Guidelines was associated with no history of smoking, current alcohol consumption, type of occupation, occupational activities, and availability of a health promotion program at work. Our findings suggest multi-level approaches (combining individual and organizational level efforts) are needed.